A Gravity Approach to Determinants of Export in a Small Open Economy: â€ŽEvidence from Jordan - Mdanat, Metri F.; Warrad, Taleb A.; Salhieh, Loay M.; Arabiyat, Talah S. (International Journal of Economics and Financial Issues, 2018)
This study seeks to identify the main factors affecting exports in small open economies. It uses panel data from 2001 to 2014 and a gravity model to identify these factors in one such economy. Our results are relevant for policymakers in small economies which engage in free trade agreements and trade liberalization to pursue economic development via trade openness and investment. We found mixed results as to theâ€ â€direction of the relationship between free trade agreements and exports, a positive â€Žcontribution of relative income in boosting exports and negative distortionary effects of distance â€Žand costs on exports.â€Ž These findings suggest that there are differential impacts of trade liberalization over time on the export performance of small open economies. Hence, policies aiming to maximize the benefits of trade agreements and reduce costs may be helpful in promoting exports. Keywords: Gravity model, Export determinants, Economic growth. JEL Classifications: F1, F13, F43